Application of the model‐informed drug development paradigm to datopotamab deruxtecan dose selection for late‐stage development - Yasong Lu; Shuang Liang; Ying Hong; Naoyuki Tajima; Kashyap Patel; Hanbin Li; David R. Wada; Jon Greenberg; Adam Petrich; Hong Zebger‐Gong; Dale Shuster; Pavan Vaddady (Wiley, 2024)
Abstract To replace the conventional maximum tolerated dose (MTD) approach, a paradigm for dose optimization and dose selection that relies on model‐informed drug development (MIDD) approaches has been proposed in oncology. Here, we report our application of an MIDD approach during phase I to inform dose selection for the late‐stage development of datopotamab deruxtecan (Dato‐DXd). Dato‐DXd is a TROP2‐directed antibody‐drug conjugate being developed for advanced/metastatic non‐small cell lung cancer (NSCLC) and other tumors. Data on pharmacokinetics (PKs), efficacy, and safety in NSCLC were collected in the TROPION‐PanTumor01 phase I dose‐expansion and ‐escalation study over a wide dose range of 0.27-10 mg/kg administered every 3 weeks. Population PK and exposure-response analyses were performed iteratively at three data cutoffs to inform dose selection. The 6 mg/kg dose was identified as the optimal dose by the second data cutoff analysis and confirmed by the subsequent third data cutoff analysis. The 6 mg/kg dose was more tolerable (i.e., lower rates of interstitial lung disease, stomatitis, and mucosal inflammation) than the MTD (8 mg/kg) and was more efficacious than 4 mg/kg (simulated mean objective response rate: 23.8% vs. 18.6%; mean hazard ratio of progression‐free survival: 0.74) - a candidate dose studied just below 6 mg/kg. Therefore, the 6 mg/kg dose was judged to afford the optimal benefit-risk balance. This case study demonstrated the utility of an MIDD approach for dose optimization and dose selection.